Tagore and the feminine : a journey in translations - Tagore, Rabindranath, 1861-1941 (SAGE Publications, 2015)
This book presents a range of Rabindranath Tagore's creative works, including translations of short stories, essays, poems, memoirs, songs and plays from his vast corpus to show his conception of the feminine and gender identity that are relevant even today. The editor establishes the search for Tagore's engagement with the feminine as subject and agency, character and voice, philosophy and politics in this book. There is rich cultural interplay as Tagore muses over the contrasting social position of women in the 'East' and the 'West'. He relies on Indian traditions to understand them in the context of domestic ethics, marital institutions, parenting, empowerment, aesthetics and gender politics. The book includes new translations while presenting fresh insights into previously published works.